2011
DOI: 10.1111/j.1747-0285.2011.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Some Novel 1,4‐Dihydropyridines as Potential AntiTubercular Agents

Abstract: Recent studies showed that 1,4-dihydropyridine-3,5-dicarbamoyl derivatives with lipophilic groups have significant antitubercular activity. In this study, we have synthesized new derivatives of 1,4-dihydropyridines bearing carbmethoxy and carbethoxy group at C-3 and C-5 of the 1,4-dihydropyridine ring. In addition, 1H-pyrazole ring is substituted at C-4 position. These analogues were synthesized by multi-component Hantzsch reaction. The in vitro antitubercular activity of compounds against Mycobacterium tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…33 Additionally, PA-824, a nitroimidazopyran displayed potent in vitro activity against Mtb, a narrow spectrum of activity limited primarily to the Mtb complex with no noticeable cross-resistance to a wide range of antituberculosis drugs. 34 Keeping all these facts in mind and in continuation of our previous endeavor, [35][36][37][38][39][40][41][42] it was envisaged to design, synthesize and investigate in vitro efficacy of new prototypes including the advantage of dual pharmacophore of dihydropyrimidine and imidazole in a single molecular platform. Furthermore, molecular docking studies of most active compounds against the active site of the Mtb DHFR enzyme helped in revealing the potential mode of action through their interactions.…”
Section: Tuberculosis (Tb) Is a Global Epidemic Caused By Pathogenic mentioning
confidence: 99%
“…33 Additionally, PA-824, a nitroimidazopyran displayed potent in vitro activity against Mtb, a narrow spectrum of activity limited primarily to the Mtb complex with no noticeable cross-resistance to a wide range of antituberculosis drugs. 34 Keeping all these facts in mind and in continuation of our previous endeavor, [35][36][37][38][39][40][41][42] it was envisaged to design, synthesize and investigate in vitro efficacy of new prototypes including the advantage of dual pharmacophore of dihydropyrimidine and imidazole in a single molecular platform. Furthermore, molecular docking studies of most active compounds against the active site of the Mtb DHFR enzyme helped in revealing the potential mode of action through their interactions.…”
Section: Tuberculosis (Tb) Is a Global Epidemic Caused By Pathogenic mentioning
confidence: 99%
“…Compounds derived from xanthenes and 1,4-dihydropyridines (1,4-DHPs), such as 1,8-dioxo-octahydroxanthenes and 1,8-dioxodecahydroacridines, are of importance as they have various biological activities such as antibacterial [25], antiinflammatory [26], antimicrobial [27], antitubercular [28], neuroprotectant [29], and insecticidal activities [30]. A number of xanthenes found uses in laser technologies [31], dyes [32], and fluorescent materials for visualization of biomolecules [33].…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] It has been demonstrated that the type of C-3, C-4 and C-5 substituent and the lipophilicity of the molecule have important effects on the antimicrobial activity of 1, 4-dihydropyridine compound. [19] 1,4-DHP derivatives containing diethyl carbamoyl and ester substituents at C-3 and C-5, and substituted aromatic or heteroaromatic ring at C-4 position have also been reported as potential antimicrobial agents. [20,21] N-1 (substituted) phenyl substitution exists in the structure of some of the antimicrobial 1,4-DHPs.…”
Section: Introductionmentioning
confidence: 99%